Canais formais de comunicação do conhecimento antropológico produzido no Brasil - Oliveira, Marlene de (1988)
The study aims to identify communication channels in Anthropology. CAPES "Sistema de Acompanhamento e Avaliação" data base for the gathering of data related to eight pos-graduate courses in Anthropology was used. Three variables were chosen for the execution of the work: a) Organizations, b) Teaching staff (teachers/researchers), c)Bibliographic production. Preliminary results were submitted for appreciation by members of the community of anthropologists in order to obtain qualitative analysis of statisticaal data. The final result of the analysis revealed three types of communication channels: formal, semi-formal and others in the area. Emphasis was given to the formal channels employed: serials and monographs. It was found that the nature of the scientific discipline determines the characteristics of formal communication channels.